Scenario-Based Risk Assessment for Düzce Province - Zeynep Mıhçı; Hüseyin Bayraktar (Doğal Afetler ve Çevre Dergisi)
However, following the earthquake event of 12 November 1999, 80% of the built environment in the Düzce area had been destroyed and after the removal of the ruins, it was transformed into a huge open space. Subsequently, on 9 December 1999, Düzce was declared the provincial capital city, having 20 neighborhoods, 97 villages, and 7 districts under its administration. The main components featured in this study are 10 urban neighborhoods of Düzce that are all comprised of structural and natural environments located in the vicinity of the North Anatolian Fault Line. These areas are briefly defined and some benefits from their restructuring as viewed within this framework are presented. The most important result we obtained as a result of the earthquake scenario prepared for Düzce province; The fact that the ten neighborhoods we examined in the central district of Düzce are at a critical point on the fault line and Most of the buildings here were affected by the 17 August 1999 Izmit Gulf earthquake, If the buildings encounter a possible earthquake of this magnitude, it may be effective in the high number of dead and injured. Another important finding is; The main purpose of earthquake risk analyzes is to determine the number of tents that may be needed in advance and the area required for the tent. As a result; This study, which was carried out in the central district of Düzce province, will ensure that the necessary precautions are taken beforehand in case of a possible earthquake, and that the loss of life will be reduced to a minimum by acting more planned and faster at that time.